Composition, negative electrode, and battery

JP2025036342AActive Publication Date: 2025-03-14LARGAN MEDICAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024147719
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2024-08-29
Publication Date
2025-03-14
Estimated Expiration
2044-08-29

AI Technical Summary

Benefits of technology

【0004】 本開示は、特定の材料を用いてコアシェル構造を形成し、且つさらに負極及び電池を製造し、電池が大きな電流密度に適応し且つ全体構造の完全性を維持することに寄与し、電池の充電安定性及び全体電気容量を高めることに寄与する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036342000001_ABST
    Figure 2025036342000001_ABST
Patent Text Reader

Abstract

To provide a composition.SOLUTION: The composition includes a core-shell structure including a core material and a shell material. The shell material is farther away from a center of the core-shell structure than the core material. The core material includes a structural element oxide. The structural element oxide includes a structural element, the structural element being at least two selected from the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel. The shell material includes a mixed material, the mixed material including a modified silicon material. The modified silicon material includes a silicon-based material and a polymer. When specific conditions are met, the composition contributes to the improvement of battery safety, service life, stability, and electrical capacity.SELECTED DRAWING: Figure 2A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a composition, an anode, and a battery, and in particular to a composition, an anode, and a battery that can improve battery safety, service life, stability, and electric capacity. [Background technology]

[0002] The research and development of conventional batteries is aimed at high energy density, high working voltage, fast charging speed and long cycle life, and the currently commonly used negative electrode material is carbon or graphite. In the cycle process using large current, carbon or graphite, which is mostly layered structure, cannot withstand the rapid absorption and release of ions, and is prone to irreversible collapse of structure, reducing electric capacity and storage life, and when the current density is too large, polarization phenomenon is likely to occur, and lithium ions are reduced to lithium metal on the sheet surface and form lithium dendrites, which leads to short circuit inside the battery, and there are safety doubts. Summary of the Invention [Problem to be solved by the invention]

[0003] In addition, the theoretical energy density of graphite is much lower than the kinetic energy demand of large power devices such as electric vehicles, so the introduction of silicon-based materials with high energy density as new negative electrode materials has become the development trend of subsequent lithium batteries. However, research has shown that after multiple charge and discharge cycles, batteries with silicon-based materials will have lithium ions absorbed and released repeatedly inside the silicon-based materials, resulting in excessive volume change and material rupture, which will seriously affect the structural stability of the negative electrode and result in obvious loss of battery life. [Means for solving the problem]

[0004] The present disclosure uses specific materials to form a core-shell structure and further fabricate anodes and batteries, which contribute to the battery accommodating large current densities and maintaining the integrity of the overall structure, and contribute to increasing the charging stability and overall electrical capacity of the battery.

[0005] According to the present disclosure, there is provided a composition comprising a core-shell structure including a core material and a shell material, the shell material being further from the center of the core-shell structure than the core material, the core material including a structural element oxide, the structural element oxide including a structural element, the structural element being at least two selected from the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese, and nickel, the shell material including a mixed material, the mixed material including a modified silicon material, and the modified silicon material including a silicon-based material and a polymer.

[0006] According to the present disclosure, there is provided a negative electrode comprising the composition described in the preceding paragraph.

[0007] According to the present disclosure, there is provided a battery including the negative electrode described in the preceding paragraph.

[0008] According to the present disclosure, there is provided a composition having a core-shell structure including a core material and a shell material, wherein the shell material is farther from a center of the core-shell structure than the core material, the core material includes a structural element oxide, the structural element oxide includes a niobium titanium composite oxide, the shell material includes a mixed material, and the mixed material includes a silicon-based material, and when the coverage rate of the silicon-based material to the core material is PCs, the composition satisfies the condition of 20.0%≦PCs≦100.0%.

[0009] According to the present disclosure, there is provided a negative electrode comprising the composition described in the preceding paragraph.

[0010] According to the present disclosure, there is provided a battery including the negative electrode described in the preceding paragraph.

[0011] According to the present disclosure, there is provided a composition having a core-shell structure including a core material and a shell material, the shell material being farther away from the center of the core-shell structure than the core material, the core material being at least one selected from the group consisting of a carbon active material, a mixed oxide of structural elements, and a tin-based alloy, the shell material including a mixed material, the mixed material including a modified silicon material, the modified silicon material including a silicon-based material and a polymer, the polymer including a siloxane group, where D50 is defined as a particle size at which the percentage of the cumulative particle size distribution reaches 50%, cD50 is the particle size of the core material at D50, and sD50 is the particle size of the silicon-based material at D50, and the composition satisfies the condition 1.0≦cD50 / sD50≦8000.0. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a scanning electron microscope image of the surface of the core-shell structure of the battery of the comparative example. [Figure 2A] FIG. 2 is a scanning electron microscope image of the surface of the core-shell structure of the battery of the first embodiment. [Figure 2B] FIG. 2 is a scanning electron microscope image of an area of ​​0.02×πR2 μm2 on the surface of the core-shell structure of the first embodiment. [Diagram 3] FIG. 2 is an image showing the element position distribution on the surface of the core-shell structure of the first embodiment. [Figure 4] 1 is a result of superimposing a scanning electron microscope image and an element position distribution image of the surface of the core-shell structure of the first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present disclosure provides a composition comprising a core-shell structure including a core material and a shell material, the shell material being further from the center of the core-shell structure than the core material, the center being capable of representing the core of the core-shell structure in three-dimensional space.

[0014] The core material includes a structural element oxide, the structural element oxide includes a structural element, the structural element being at least two selected from the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese, and nickel. The shell material includes a mixed material, the mixed material includes a modified silicon material, the modified silicon material includes a silicon-based material and a polymer.

[0015] Alternatively, the core material includes a structural element oxide, the structural element oxide includes a niobium titanium composite oxide, the shell material includes a mixed material, and the mixed material includes a silicon-based material.

[0016] Or, the core material is at least one selected from the group consisting of carbon active material, structural element mixed oxide and tin-based alloy. The shell material comprises a mixed material, the mixed material comprises a modified silicon material, the modified silicon material comprises a silicon-based material and a polymer, and the polymer comprises a siloxane group.

[0017] Thus, the present disclosure uses the principle of opposite charge attraction and heteroaggregation to form a core-shell structure by self-assembly of a core material with a large particle size and a shell material with a small particle size. This not only simplifies the process and improves the overall contact area between the core material and the shell material, but also contributes to strengthening the stability of the core-shell structure and improving the energy density. The core material may be a compound formed by at least two of the above structural elements, and may have high electrical conductivity, which contributes to strengthening the fast charging performance of the battery and effectively reducing the resistance value, high mechanical stability, which contributes to the battery adapting to a large current density and maintaining the integrity of the overall structure, and high heat resistance, which contributes to improving the safety and service life of the battery in a high-temperature environment. The shell material may include a silicon-based material, and the surface modification of the silicon-based material with a polymer allows the polymer to form an elastic film around the silicon-based material, effectively providing a binding effect and contributing to reducing the problem of the silicon-based material bursting due to the large volume change. The polymer is electrically chargeable, which contributes to improving the dispersion of the silicon-based material, and coats the outer surface of the core material more uniformly and tightly, improving the coverage rate, avoiding the decrease in conductivity of the inner region caused by the aggregation of too much silicon-based material, and is less likely to cause oxidation and reduction, resulting in irreversible capacity loss. The core material is selected from carbon active materials, which contributes to improving the conductivity of the silicon-based material, and the material is selected from structural element mixed oxides or tin-based alloys, which contributes to improving the stability of battery charging and the overall capacity.

[0018] When the coverage rate of the silicon-based material to the core material is PCs, the condition of 20.0%≦PCs≦100.0% is satisfied. By improving the coverage rate of the silicon-based material, not only the stress caused by the volume expansion due to the aggregation phenomenon of the silicon-based material is reduced, but also the dispersibility of the silicon-based material is improved. The outer peripheral surface layer of the core material can be covered more uniformly and tightly, which improves the contact area between the core material and the entire silicon-based material, and contributes to improving the electrical conductivity and energy density. It can also satisfy the condition of 40.0%≦PCs≦95.0%. It can also satisfy the condition of 25.0%≦PCs≦98.0%. It can also satisfy the condition of 30.0%≦PCs≦96.0%. It can also satisfy the condition of 35.0%≦PCs≦94.0%. It can also satisfy the condition of 40.0%≦PCs≦92.0%. It can also satisfy the condition of 45.0%≦PCs≦90.0%.

[0019] When the particle size of the core material at D50 is cD50 and the particle size of the silicon-based material at D50 is sD50, the condition of 1.0≦cD50 / sD50≦8000.0 is satisfied. The particle size of the core material and the particle size of the silicon-based material have an appropriate size ratio, which contributes to the silicon-based material coating the outer surface layer of the core material more uniformly and tightly. It can also satisfy the condition of 50.0≦cD50 / sD50≦500.0. It can also satisfy the condition of 10.0≦cD50 / sD50≦5000.0. It can also satisfy the condition of 20.0≦cD50 / sD50≦1000.0. It can also satisfy the condition of 30.0≦cD50 / sD50≦800.0. It can also satisfy the condition of 35.0≦cD50 / sD50≦500.0. It can also satisfy the condition: 40.0≦cD50 / sD50≦300.0.

[0020] If the particle diameter of the core material at D50 is cD50, it can satisfy the condition of 100.0 nm ≦ cD50 ≦ 80000.0 nm. By selecting a core material with an appropriate particle diameter, it contributes to reducing the time required for ion conduction and enhancing the magnification performance. It can also satisfy the condition of 200.0 nm ≦ cD50 ≦ 70000.0 nm. It can also satisfy the condition of 400.0 nm ≦ cD50 ≦ 50000.0 nm. It can also satisfy the condition of 600.0 nm ≦ cD50 ≦ 40000.0 nm. It can also satisfy the condition of 800.0 nm ≦ cD50 ≦ 30000.0 nm. It can also satisfy the condition of 1000.0 nm ≦ cD50 ≦ 20000.0 nm.

[0021] If the particle size of the silicon-based material in D50 is sD50, it can satisfy the condition of 10.0 nm ≦ sD50 ≦ 3000.0 nm. By selecting a silicon-based material with a small particle size, it contributes to reducing the stress caused by the volume expansion of the silicon-based material. It can also satisfy the condition of 10.0 nm ≦ sD50 ≦ 10000.0 nm. It can also satisfy the condition of 10.0 nm ≦ sD50 ≦ 2000.0 nm. It can also satisfy the condition of 10.0 nm ≦ sD50 ≦ 1000.0 nm. It can also satisfy the condition of 10.0 nm ≦ sD50 ≦ 500.0 nm. It can also satisfy the condition of 20.0 nm ≦ sD50 ≦ 400.0 nm. It can also satisfy the condition of 30.0 nm ≦ sD50 ≦ 300.0 nm. Also, it can satisfy the condition of 40.0 nm ≦ sD50 ≦ 250.0 nm. Also, it can satisfy the condition of 50.0 nm ≦ sD50 ≦ 200.0 nm. Also, it can satisfy the condition of 60.0 nm ≦ sD50 ≦ 150.0 nm. Also, it can satisfy the condition of 70.0 nm ≦ sD50 ≦ 100.0 nm.

[0022] The weight of the core material in the core-shell structure may be greater than the weight of the silicon-based material in the core-shell structure. By providing an appropriate weight ratio between the core material and the silicon-based material in the core-shell structure, it contributes to maintaining a balance between the stability of the core-shell structure and the improvement of the energy density.

[0023] The structural element oxide may be a niobium titanium composite oxide. During the lithium absorption process, the niobium titanium composite oxide has a small crystal volume change and high mechanical stability, so that it can accommodate a large current density and maintain the integrity of the entire structure, and avoid the problem of the deterioration of the battery cycle life caused by the structure damage.

[0024] If the weight of the niobium titanium composite oxide for the core-shell structure is Wtn and the weight of the silicon-based material for the core-shell structure is Ws, it can satisfy the condition of 10.0≦Wtn / Ws≦500.0. By constructing the niobium titanium composite oxide and the silicon-based material in an appropriate ratio, it contributes to improving the charging efficiency and energy density of the battery. It can also satisfy the condition of 20.0≦Wtn / Ws≦300.0, thereby contributing to strengthening the stability of the battery and improving the energy density during the large current charge and discharge process. It can also satisfy the condition of 25.0≦Wtn / Ws≦280.0. It can also satisfy the condition of 30.0≦Wtn / Ws≦260.0. It can also satisfy the condition of 35.0≦Wtn / Ws≦240.0. It can also satisfy the condition of 38.0≦Wtn / Ws≦220.0. It can also satisfy the condition 40.0≦Wtn / Ws≦210.0.

[0025] The niobium titanium composite oxide may be a doped niobium titanium composite oxide. Doping changes the chemical properties of the niobium titanium composite oxide, reduces the difficulty of electron and ion movement, and contributes to improving the electrical conductivity of the niobium titanium composite oxide.

[0026] The doped niobium titanium composite oxide may include at least one doping element, and the at least one doping element may be selected from at least one of the group consisting of lithium, manganese, magnesium, iron, copper, cobalt, gallium, tantalum, tungsten, fluorine, phosphorus, sodium, and molybdenum. By selecting and doping an element with high conductivity, it contributes to improving the conductivity of the doped niobium titanium composite oxide and enhancing the rapid charging performance of the battery, or by selecting and doping a light element, it contributes to improving the energy density.

[0027] The at least one doping element may be selected from the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus. Doping with the doping element maintains the reversibility of the lithium ions being absorbed and released into the niobium titanium composite oxide structure during the oxidation-reduction process, and contributes to reducing the increase in resistance value after multiple oxidation-reduction cycles.

[0028] The polymer may be polymerized by at least two kinds of monomers, and the at least two kinds of monomers may include a first monomer and a second monomer. The first monomer may include a siloxane group, and the second monomer may include a carboxyl group or an ester group, and the first monomer may be closer to a silicon-based material than the second monomer. The first monomer and the silicon-based material are condensed to form a strong siloxane structure, which contributes to maintaining the integrity of the polymer. The first monomer and the second monomer include unsaturated functional groups, which form a polymeric polymer by addition polymerization and copolymerization reaction of multiple monomers, which contributes to strengthening the protective ability of the polymeric polymer.

[0029] The silicon-based material and the polymer may be covalently bonded to the outer peripheral surface of the silicon-based material to form a polymer protective layer, and the polymer has the advantage of elasticity, which can adapt to the sudden volume change of the silicon-based material during charging and discharging and maintain the integrity of the entire structure.

[0030] The mixed material may further include a carbon-based material. The addition of the carbon-based material to the shell material contributes to improving the conductive efficiency of the battery.

[0031] If the total number of particles of the niobium titanium composite oxide in the core-shell structure is Qtn and the total number of particles of the silicon-based material in the core-shell structure is Qs, it can satisfy the condition of 0.1≦Log(Qs / Qtn)<10.0. The niobium titanium composite oxide and the silicon-based material have an appropriate particle total number ratio in the core-shell structure, which contributes to improving the coverage rate of the silicon-based material and reducing the ratio of a part of the silicon-based material that is not adsorbed by the niobium titanium composite oxide. It can also satisfy the condition of 2.5≦Log(Qs / Qtn)≦7.5. It can also satisfy the condition of 0.5≦Log(Qs / Qtn)≦9.0. It can also satisfy the condition of 1.0≦Log(Qs / Qtn)≦8.0. It can also satisfy the condition of 1.5≦Log(Qs / Qtn)≦7.0. It can also satisfy the condition of 2.0≦Log(Qs / Qtn)≦6.0. In addition, it can satisfy the condition: 3.0≦Log(Qs / Qtn)≦6.5, and it can satisfy the condition: 3.2≦Log(Qs / Qtn)≦6.0.

[0032] If the particle size of the niobium titanium composite oxide is Dtn and the particle size of the silicon-based material at D50 is sD50, it can satisfy the condition of 20.0≦Dtn / sD50≦500.0. The particle size of the niobium titanium composite oxide and the particle size of the silicon-based material have an appropriate dimensional ratio, which contributes to improving the coverage rate and the energy density. It can also satisfy the condition of 25.0≦Dtn / sD50≦450.0. It can also satisfy the condition of 30.0≦Dtn / sD50≦400.0. It can also satisfy the condition of 35.0≦Dtn / sD50≦350.0. It can also satisfy the condition of 40.0≦Dtn / sD50≦300.0. It can also satisfy the condition of 45.0≦Dtn / sD50≦250.0.

[0033] The present disclosure further provides a negative electrode of the above composition.

[0034] If the weight of the core material in the negative electrode is tWc and the weight of the silicon-based material in the negative electrode is tWs, it can satisfy the condition of 0.1≦tWc / tWs≦100.0. The core material and the silicon-based material are structured in a suitable weight ratio to form the negative electrode, which contributes to enhancing the stability of the battery and improving the energy density during high-current charging and discharging. It can also satisfy the condition of 0.2≦tWc / tWs≦80.0. It can also satisfy the condition of 0.4≦tWc / tWs≦60.0. It can also satisfy the condition of 0.6≦tWc / tWs≦50.0. It can also satisfy the condition of 0.7≦tWc / tWs≦40.0. It can also satisfy the condition of 0.8≦tWc / tWs≦30.0.

[0035] The present disclosure further provides a battery including the above-described negative electrode.

[0036] If the maximum value of the discharge volume capacity of the battery from the 1st cycle to the 20th cycle is VMax, it is 100 mAh / cm 3≦VMax≦800mAh / cm 3 Measuring the maximum capacity of the battery after the battery reaches a steady state by measuring the maximum capacity of the battery after the previous 20 cycles. It also helps to confirm the capacity of the battery after the battery reaches a steady state. It is 120mAh / cm 3 ≦VMax≦750mAh / cm 3 It can also meet the condition of 140mAh / cm 3 ≦VMax≦720mAh / cm 3 It can also meet the condition of 160mAh / cm 3 ≦VMax≦700mAh / cm 3 It can also meet the condition of 180mAh / cm 3 ≦VMax≦680mAh / cm 3 It can also meet the condition of 200mAh / cm 3 ≦VMax≦650mAh / cm 3 The condition can be satisfied.

[0037] If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 10th cycle is V10, it can satisfy the condition of 0.85≦V10 / V5. Comparing the difference between the electric capacity of the battery at the 5th cycle and the electric capacity after the short-term cycle number contributes to judging the durability of the battery. It can also satisfy the condition of 0.88≦V10 / V5≦1.30. It can also satisfy the condition of 0.90≦V10 / V5≦1.25. It can also satisfy the condition of 0.92≦V10 / V5≦1.20. It can also satisfy the condition of 0.95≦V10 / V5≦1.15. It can also satisfy the condition of 0.98≦V10 / V5≦1.10.

[0038] If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 50th cycle is V50, it can satisfy the condition of 0.80≦V50 / V5. Comparing the difference between the electric capacity of the battery at the 5th cycle and the electric capacity after the intermediate number of cycles contributes to judging the durability of the battery. It can also satisfy the condition of 0.85≦V50 / V5≦1.30. It can also satisfy the condition of 0.88≦V50 / V5≦1.25. It can also satisfy the condition of 0.90≦V50 / V5≦1.20. It can also satisfy the condition of 0.92≦V50 / V5≦1.15. It can also satisfy the condition of 0.95≦V50 / V5≦1.10.

[0039] If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 100th cycle is V100, it can satisfy the condition of 0.70≦V100 / V5. Comparing the difference between the electric capacity of the battery at the 5th cycle and the electric capacity after a long cycle number contributes to the basis for judging the battery life. It can also satisfy the condition of 0.75≦V100 / V5≦1.35. It can also satisfy the condition of 0.80≦V100 / V5≦1.30. It can also satisfy the condition of 0.85≦V100 / V5≦1.25. It can also satisfy the condition of 0.90≦V100 / V5≦1.20. It can also satisfy the condition of 0.95≦V100 / V5≦1.15.

[0040] If the total number of times that the coulombic efficiency of the previous 20 cycles of the battery is greater than 90% and less than 110% is n90E20, it can satisfy the condition of 15≦n90E20≦20. The coulombic efficiency of the previous cycles all achieves a high standard, which contributes to reducing the impact of lithium loss on the capacity retention rate. It can also satisfy the condition of 16≦n90E20≦20. It can also satisfy the condition of 17≦n90E20≦20. It can also satisfy the condition of 18≦n90E20≦20. It can also satisfy the condition of 19≦n90E20≦20. It can also satisfy the condition of n90E20=20.

[0041] The compositions described in this disclosure may include a core-shell structure and a supplemental material.

[0042] The core-shell structure described in the present disclosure may include a core material and a shell material, and a major portion of the shell material may be located further away from the center of the core-shell structure than the core material, and the shell material may be located at the periphery of the core material, and if there is a pore structure on the surface of the core material particle, some of the shell material may be located within the pore structure on the surface of the particle. The major portion may be expressed as 50% or more of all the shell material.

[0043] The core material described in the present disclosure may be a structural element oxide, a carbon active material or a tin-based alloy, and the structural element oxide may include a structural element complex oxide and a structural element mixed oxide.

[0044] The structural element complex oxide may include a structural element, and the structural element may be selected from a compound formed by at least two of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese, and nickel, such as a lithium titanium complex oxide, a niobium titanium complex oxide, and a tin complex oxide. More specifically, the structural element complex oxide is a compound formed by at least three of the structural elements.

[0045] The structural element mixed oxide may include a structural element, and the structural element may be selected from lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese and nickel.To further explain, the structural element mixed oxide may be a mixture formed by at least two kinds of oxides containing a structural element, such as a mixture formed by tin oxide and nickel oxide, a mixture formed by tin oxide and titanium oxide, a mixture formed by tin oxide and cobalt oxide, a mixture formed by tin oxide and manganese oxide, a mixture formed by silicon oxide and lithium oxide, a mixture formed by silicon oxide and titanium oxide, a mixture formed by silicon oxide and tin oxide, or a mixture formed by silicon oxide and iron oxide.To further explain, the structural element mixed oxide may be a mixture formed by at least three kinds of oxides containing a structural element.

[0046] The carbon active material described in this disclosure may be graphite, graphene, carbon microspheres, hard carbon, or soft carbon.

[0047] The shell materials described herein may be composite materials, which may include modified silicon materials and carbon-based materials, and which may include modified silicon materials and silicon-based materials and auxiliary materials.

[0048] The core-shell structure composition method described in the present disclosure can form a colloidal solution by adding a core material and a shell material to a solution, the core material and the shell material have different charges and can attract each other in the solution, and the particle size of the core material is larger than the particle size of the shell material, and the shell material can be densely distributed around the periphery of the core material to form a core-shell structure. To be more specific, the chargeability and charge amount of the core material or the shell material can be changed by adjusting the electrolyte added to the solution, the pH value of the solution, etc., so that the core material can be positively charged and the shell material can be negatively charged and can attract each other, or the core material can be negatively charged and the shell material can be positively charged and can attract each other. To be more specific, the shell material can be electrically charged using a surface-modified silicon-based material, and can be attracted to the core material with a different charge, and the periphery of the core material can be coated with a carbon-based material.

[0049] The coverage rate described in the present disclosure, in which the coverage rate of the silicon-based material to the core material, is positively correlated with the weight ratio of the precursor of the core-shell structure added until saturation. With an increase in the added ratio of the silicon-based material, the coverage rate of the surface or pores of the core material covered by the silicon-based material increases, and the thickness of the shell material also increases. The coverage rate can be calculated in the following manner: A surface image of the core-shell structure is generated by scanning electron microscope (SEM) technology, and a position distribution image map of the region surface elements is obtained by energy dispersive X-ray spectrum (EDX) imaging analysis. The surface image of the core-shell structure and the position distribution image map of the region surface elements are superimposed, and the color, brightness and shape differences of the superimposed images are analyzed by image software (e.g., ImageJ). The particle size of the core material is R (μm), and 0.02×πR 2 (μm 2) the proportion of the area occupied by the silicon-based material in the area, and thus the coverage rate of the silicon-based material to the core material can be obtained. The surface image of the core-shell structure can be generated by transmission electron microscope (TEM) technology, and the position distribution image diagram of the area surface elements can be obtained by X-ray photoelectron spectroscopy (XPS) imaging analysis. The criteria are as follows: for the core-shell structure, an independent and completely visible core-shell structure is selected, a shell structure without obvious defects and distributed uniformly is selected, the selected analysis area must include the sphere center, the calculation of the single particle diameter of the core material is the measurement of the average value of the longest side and the shortest side, and the particle diameter and coverage rate obtained by this method are all measured and calculated by two-dimensional images.

[0050] The ratio of the total number of particles of the shell material and the total number of particles of the core material described in this disclosure is Np. According to the theoretical calculation method, the core material and the shell material are spheres, the total number of particles of the core material is 1, the particle diameter of the core material is R, the particle diameter of the shell material is r, the shell material is distributed on the surface of the core material in the densest pile, the surface area of ​​the virtual spherical shell formed by the spherical center of the shell material is A, when the shell material is distributed in the densest pile, the surface area of ​​the equilateral triangle of the spherical centers of three adjacent shell materials connected together is a, each equilateral triangle can provide 0.5 shell material, and the coverage rate of the shell material is PC, and its Np can be calculated in the following manner:

number

number

number

[0051] The niobium-titanium composite oxide described in the present disclosure may include an undoped niobium-titanium composite oxide and a doped niobium-titanium composite oxide. The composition components of the undoped niobium-titanium composite oxide include at least niobium element, titanium element, and oxygen element. The niobium-titanium composite oxide includes a plurality of compounds and can be further represented by the following chemical formula. Ti x Nb y O z , z ≦ 4x + 5y, for example, TiNb2O7, Ti2Nb 10 O 29 , TiNb 14 O 37 and TiNb 24 O 62 . The crystal structure of the niobium-titanium composite oxide may be cubic, monoclinic, orthorhombic, ReO3-type lattice, or a layered structure, etc. The doped niobium-titanium composite oxide may be selected from those in which at least one doping element is doped into at least one compound of the above undoped niobium-titanium composite oxide and can be further represented by the following chemical formula. Ti (x-a) M1 a Nb (y-b) M2 b O (z-c) M3 c , M1, M2, and M3 are doping elements, 0 ≦ a < x, 0 ≦ b < y, 0 ≦ c < z. The structure can be changed by adjusting the doping element or doping ratio. Furthermore, at least one auxiliary material can be selected to coat or fill the surface or pores of the niobium-titanium composite oxide.

[0052] The lithium-titanium composite oxide described in the present disclosure may include an undoped lithium-titanium composite oxide and a doped lithium-titanium composite oxide. The composition components of the undoped lithium-titanium composite oxide include at least lithium element, titanium element, and oxygen element. The lithium-titanium composite oxide includes various compounds, such as Li4Ti5O12 , LiTi2O4, Li2Ti3O7 and Li2TiO3. The doped lithium titanium composite oxide may be selected from at least one compound of the above non-doped lithium titanium composite oxides doped with at least one doping element, and the structure can be changed by adjusting the doping element or doping ratio, and at least one auxiliary material can be selected to cover or fill the surface or pores of the lithium titanium composite oxide.

[0053] The doping element described in the present disclosure may be selected from any one of the elements of Group IA, Group IIA, Group IVB, Group VB, Group VIB, Group VIIB, Group VIIIB, Group IB, Group IIB, Group IIIA, Group IVA, Group VA, Group VIA, and Group VIIA. It may also be selected from at least one of lithium, boron, fluorine, sodium, magnesium, aluminum, silicon, phosphorus, sulfur, chlorine, calcium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, arsenic, bromine, zirconium, molybdenum, antimony, iodine, tantalum, tungsten, and bismuth. By selecting and doping a highly conductive element or a light element, it contributes to improving the conductivity of the doped niobium titanium composite oxide, enhancing the fast charging performance of the battery, and improving the energy density.

[0054] The tin-based composite oxide described in the present disclosure may include tin-nickel composite oxide, tin-iron composite oxide, tin-copper composite oxide, tin-titanium composite oxide, tin-niobium composite oxide, tin-cobalt composite oxide, tin-silicon composite oxide, tin-manganese composite oxide, and tin-lithium composite oxide.

[0055] Tin-based alloys described herein may include tin phosphorus alloys, tin sulfur alloys, tin antimony alloys, tin cobalt sulfur alloys, tin antimony sulfur alloys, and tin copper phosphorus alloys.

[0056] The modified silicon material described in the present disclosure may include a silicon-based material and an auxiliary material, and the silicon-based material may form a mixture with the auxiliary material, may form a chemical bond with the auxiliary material, or may form a membrane layer structure with the auxiliary material. To further explain, the auxiliary material may be selected as a polymer. The polymer may be chemically bonded or physically mixed to form a membrane layer structure around the silicon-based material, and the polymer may be polymerized by at least two kinds of monomers, and the at least two kinds of monomers may include a first monomer and a second monomer. The first monomer includes a siloxane group, and the second monomer includes a carboxyl group or an ester group, and the first monomer is closer to the silicon-based material than the second monomer, and the unsaturated alkenyl group or acrylate group included in the first monomer and the unsaturated alkenyl group or the unsaturated acrylate group included in the second monomer may be covalently bonded to form a polymer by addition polymerization and copolymerization reaction. A crosslinking agent may be further added to the polymer to bond and crosslink the linear polymers to each other to form a network structure.

[0057] The silicon-based material described in the present disclosure may be silicon, silicon oxide, silicon carbon composite, or silicon alloy. If the particle size of the silicon-based material at D50 is sD50, sD50 may be 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 800nm, 1000nm, 1500nm, 2000nm, 2500nm, or 3000nm.

[0058] The first monomer described in the present disclosure has at least one alkenyl group (-C=C-), carbonyl group (-C=O), carboxyl group (-COOH), amide group (-CONH2) or silyl enol ether (SEN) group.The siloxy compound may be a siloxy compound containing ether, such as ethenyl(trimethoxy)silane, ethenyl(triethoxy)silane, ethenyl-dimethoxy-methylsilane, 2-(chloromethyl)prop-2-enyl-trimethoxysilane, [2-hydroxy-3-[3-[methyl-bis(trimethylsilyloxy)silyl]propoxy]propyl]2-methylprop-2-enoate, 3-[dimethyl(trimethylsilyloxy)silyl]propyl 2-methylprop-2-enoate, and the like. Dimethyl(trimethylsilyloxy)silyl]propyl 2-methylprop-2-enoate, 3-[Methyl-bis(trimethylsilyloxy)silyl]propyl 2-methylprop-2-enoate, N-Prop-2-enyl-3-trimethoxysilylpropan-1-amine, (3-Isocyanatopropyl)-triethoxysilane, 1-[3-(Trimethoxysilyl)propyl]urea, and vinylmethylsiloxane-dimethylsiloxane silanol terminated copolymer. The siloxy compound may have, for example, the following structure, but is not limited thereto: (R)3-Si-(CH2) n -X-(CH2) m -A、 R is selected from the group consisting of methoxy, ethoxy and siloxy, X is methyl or oxy, A is selected from the group consisting of vinyl, acrylate and methacrylate, and n and m satisfy the condition: 0≦n+m≦10. The siloxy compounds are (meth)acryloylmethyl trimethoxysilane (Triethoxysilylmethyl 2-methylprop-2-enoate), (meth)acryloylethyl trimethoxysilane (2-Trimethylsilyloxyethyl 2-methylprop-2-enoate), (meth)acryloylpropyl trimethoxysilane (3-Trimethoxysilylpropyl 2-methylprop-2-enoate, MPS), (meth)acryloylbutyl trimethoxysilane (4-Trimethoxysilylbutyl 2-methylprop-2-enoate), (meth)acryloylpentyl trimethoxysilane (5-Trimethoxysilylpentyl 2-methylprop-2-enoate), (meth)acryloylhexyl trimethoxysilane (6-Trimethoxysilylhexyl 2-methylprop-2-enoate), (meth)acryloylheptyl trimethoxysilane (7-Trimethoxysilylheptyl 2-methylprop-2-enoate), (meth)acryloyloctyltrimethoxysilane (8-trimethoxysilyloctyl 2-methylprop-2-enoate), (meth)acryloylnonyltrimethoxysilane (9-trimethoxysilylnonyl 2-methylprop-2-enoate), (meth)acryloyldecyltrimethoxysilane (10-trimethoxysilyldecyl 2-methylprop-2-enoate), tris(trimethylsilyloxy)silylmethyl 2-methylprop-2-enoate, 3-tris(trimethylsilyloxy)silylpropyl 2-methylprop-2-enoate.Siloxy compounds form active silanol (Si-OH) through hydrolysis, and can form siloxane compounds (siloxane) with silicon-oxygen-silicon (Si-O-Si) structure through condensation reaction with silicon-based materials (especially those that form silicon oxide on the surface by oxidizing agents). The oxidizing agents can oxidize the silicon-hydrogen bond (Si-H) on the surface of silicon-based materials to silanol (Si-OH), or oxidize silicon to silica, contributing to the formation of an oxide layer on the surface of silicon-based materials.

[0059] The second monomer described herein may include a carboxyl or ester, such as dimethylaminoethyl acrylate (2-(Dimethylamino)ethyl 2-methylprop-2-enoate, DMAEMA), methyl methacrylate (MMA), methyl prop-2-enoate (MA), isooctyl acrylate (2-Ethylhexyl prop-2-enoate, 2EHA), prop-2-enoic acid (AA), isobutyl methacrylate (2-methylpropyl 2-methylprop-2-enoate, IBMA), benzyl methacrylate (Benzyl 2-methylprop-2-enoate, BZMA), tetrahydrofurfuryl acrylate (Oxolan-2-ylmethyl prop-2-enoate, THFA), ethoxyethoxyethyl acrylate (2-(2-Ethoxyethoxy)ethyl prop-2-enoate (EDGA), dodecyl methacrylate (dodecyl prop-2-enoate (LA) or a combination of the above monomers.

[0060] The crosslinking agents described in this disclosure are capable of linking and crosslinking linear polymers together to form a network structure, and the crosslinking agent may be any terminally ethylenically unsaturated compound.Ethylenediaminetetraacetic acid (2,2',2'',2'''-(ethane-1,2-diyldinitrilo)tetraacetic acid, EDTA), ethoxylated-9 trimethylolpropane triacrylate, TMP9EOTA, ethylene glycol dimethacrylate, 2-(2-methylprop-2-enoyloxy)ethyl 2-methylprop-2-enoate, diethylene glycol dimethacrylate, 2-[2-(2-methylprop-2-enoyloxy)ethoxy]ethyl 2-methylprop-2-enoate, triethylene glycol dimethacrylate, 2-[2-[2-(2-methylprop-2-enoyloxy)ethoxy] ethoxy]ethyl 2-methylprop-2-enoate, tetraethylene glycol dimethacrylate, 2-[2-[2-[2-(2-methylprop-2-enoyloxy)ethoxy]ethoxy]ethyl 2-methylprop-2-enoate), allyl methacrylate (prop-2-enyl 2-methylprop-2-enoate), 1,3-propanediol dimethacrylate (3-(2-methylprop-2-enoyloxy)propyl 2-methylprop-2-enoate), 2,3-propanediol dimethacrylate ([2-methyl-3-(2-methylprop-2-enoyloxy)propyl] 2-methylprop-2-enoate), 1,4-butanediol dimethacrylate (4-(2-methylprop-2-enoyloxy)butyl 2-methylprop-2-enoate), 1,6-hexanediol dimethacrylate (6-(2-methylprop-2-enoyloxy)hexyl 2-methylprop-2-enoate).

[0061] The silicon carbon composites described in the present disclosure may include a silicon film layer structure coated with a carbon shell, a silicon carbon yolk-shell structure, and a porous structure. The silicon film layer structure coated with a carbon shell is formed by coating a carbon shell on the periphery of a silicon material by anaerobic high-temperature decomposition. The silicon carbon yolk-shell structure is formed by producing silicon oxide on the surface of silicon, coating a layer of carbon shell on the periphery of the silicon material by anaerobic high-temperature decomposition, and then removing the silicon oxide with hydrofluoric acid (HF), thereby crushing the silicon particles into fine nanoparticles. The porous structure is a silicon carbide ceramic porous material formed by the low self-diffusion coefficient of the material or the addition of a foaming material, and carbonizing the intermediate product by sintering or galvanic corrosion.

[0062] The carbon-based materials described herein can be formed by carbonizing a carbon-containing precursor by heat treatment, which may include an organic compound, which may further include sugars, asphalts, or organic polymers.

[0063] The carbon conductive material described in the present disclosure may be graphite, carbon microspheres, carbon fiber, hard carbon, soft carbon, conductive graphite (KS6, SFG6), graphene, acetylene black, Ketjenblack, carbon black (Super P), or carbon nanotube (CNT).

[0064] The auxiliary materials described in this disclosure may include polymers, metals, alloys, non-metal oxides, metal oxides, fluorides, organic compounds, adhesives, conductive agents, or additives.

[0065] The niobium titanium composite oxide described in the present disclosure is represented by TNO, (meth)acryloylpropyltrimethoxysilane is represented by MPS, dimethylaminoethyl acrylate is represented by DMAEMA, acrylic acid is represented by AA, methyl methacrylate is represented by MMA, methyl acrylate is represented by MA, and isooctyl acrylate is represented by 2EHA. All relevant structures of the core material and shell material in the composition described in the present disclosure can be used in the relevant proportions to manufacture core-shell structures, sheets and batteries for charge-discharge testing. In the present disclosure, only some of the relevant structures are shown, and tables where data does not exist or cannot be calculated are marked with "-".

[0066] The adhesives described herein may be any of polyvinylidene fluoride (Poly(1,1-difluoroethylene) (PVDF), styrene-butadiene copolymer (Styrene-butadiene rubber (SBR)), polyethylene (Poly(methylene) (PE)), polyvinyl alcohol (Poly(Ethenol) (PVA)), polyethylenepyrrolidone (Poly(1-ethenylpyrrolidin-2-one) (PVP)), polypropylene (Poly(1-methylethylene) (PP)), polyacrylonitrile (Poly(1-acrylonitrile) (PAN)), carboxymethyl cellulose (Carboxymethyl Cellulose (CMC)), polytetrafluoroethylene (Poly(1,1,2,2-tetrafluoroethylene) (PTFE), ethylene-propylene-diene terpolymer (Ethylene Propylene Diene Monomer (EPDM)), chlorosulfonated polyethylene (Hypalon Polyethylene Rubber (CSM)), or alginic acid (Alginic Acid) formed by linear polymerization of monouronic acid. acid).

[0067] The conductive agent described in the present disclosure may be graphite, conductive graphite (KS6, SFG6), graphene, acetylene black, Ketjenblack, carbon black (Super P), carbon nanotubes (CNT), carbon microspheres, carbon fibers, hard carbon, soft carbon, aluminum powder, nickel powder, titanium dioxide, potassium titanate fiber (Potassium hexatitanate, PHT), or a combination thereof.

[0068] The additives described in the present disclosure may be carbonate-based compounds, lactone cyclic esters, ether group-containing cyclic compounds, aromatic compounds, phosphorus-containing compounds, boron-containing compounds, inorganic oxides, or combinations thereof. Adding an appropriate amount of additives contributes to improving the functions of the battery, such as improving the SEI film composition, improving high-temperature and high-voltage functions, improving ion conduction ability, reducing electrolyte impedance, improving cycle stability, stabilizing the integrity of positive and negative electrode materials, and improving electrochemical stability.

[0069] The negative electrode materials described in this disclosure may include a core-shell structure, a supplemental material, a lithium-containing metal compound, a lithium-containing metal oxide, metallic lithium, or a combination thereof.

[0070] The metal salts described in this disclosure may be inorganic acid lithium salts including LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiC4BO8, LiTFSI, LiFSI, LiNO3, LiGaCl4, etc., fluorine-containing sulfonic acid lithium salts such as LiCF3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC(CF3SO2)3, LiBF2(C2O4)(LiDFOB), LiB(C2O4)2(LiBOB), or combinations of the above, and the metal salts may include a variety of different oxidation states.

[0071] The positive electrode material described in the present disclosure may be a lithium composite metal oxide containing lithium or at least one metal, such as lithium iron phosphate (LiFePO4), lithium manganese oxide (LiMnO2, LiMn2O4), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel cobalt oxide (LiNiCoO2), lithium nickel manganese oxide (LiNiMnO4), lithium manganese cobalt oxide (LiCoMnO2, LiCoMnO4), lithium nickel manganese cobalt oxide (LiNiCoMnO2, LiNiCoMnO4), or a combination thereof. The lithium composite metal oxide may include a variety of different oxidation states.

[0072] The electrolyte described in the present disclosure may be composed of metal salts, additives, organic solvents, etc., the composition ratio of the organic solvent is greater than the composition ratio of the additives, and the electrolyte state may be liquid, colloidal, or solid. The additives and organic solvents of the electrolyte may be physically mixed, and at least one of the following additives or organic solvent monomers may be selected as the polymerization precursor.

[0073] The organic solvents described in this disclosure may be carbonates, carboxylic acid esters, ethers, sulfur-containing compounds, or combinations thereof, and the organic solvents may also be used as additives.

[0074] The organic solvent described in the present disclosure contains a polymerizable olefin group in the structure and can be a monomer of the precursor of the second structure, such as 2H-1,3-Dioxol-2-one (VC), 4-Vinyl-1,3-dioxolan-2-one (VEC), 1,3-Dithiole-2-thione (Vinylene trithiocarbonate), 2,5-Dihydrothiophene-1,1-dioxide, 1-ethenylsulfonylethene, Prop-1-ene-1,3-sultone, ether group-containing cyclic compound additive, or aromatic compound additive.

[0075] The carbonate-based organic solvent (carbonate ester) described in the present disclosure may be a compound in which the hydrogen atoms of the hydroxyl groups in the carbonic acid molecule are partially or completely replaced with alkyl groups, and can be divided into cyclic carbonates and linear carbonates. The linear carbonates may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl 2,2,2-trifluoroethyl carbonate (FEMC).Cyclic carbonates include ethylene carbonate (1,3-Dioxolan-2-one, Ethylene carbonate, EC), propylene carbonate (4-Methyl-1,3-dioxolan-2-one, Propylene carbonate, PC), trimethylene carbonate (1,3-Dioxan-2-one, Trimethylene carbonate, TMC), 1,2-butylene carbonate (4-Ethyl-1,3-dioxolan-2-one, 1,2-Butylene carbonate), 2,3-butylene carbonate ((4R, 5S)-4,5-Dimethyl-1,3-dioxolan-2-one, cis-2,3-Butylene carbonate), 1,2-pentylene carbonate, and 2,3-pentylene carbonate. The polymer may include vinylene carbonate, vinylene carbonate (2H-1,3-Dioxol-2-one, Vinylene carbonate, VC), vinyl ethylene carbonate (4-Vinyl-1,3-dioxolan-2-one, Vinylethylene carbonate, VEC), fluoroethylene carbonate (4-Fluoro-1,3-dioxolan-2-one, Fluoroethylene carbonate, FEC), difluoroethylene carbonate (trans-4,5-Difluoro-1,3-dioxolan-2-one, Difluoroethylene carbonate, DFEC), vinylene trithiocarbonate (1,3-Dithiole-2-thione, Vinylene trithiocarbonate), or a combination thereof.

[0076] The carboxylic acid ester organic solvent described in the present disclosure is produced by an esterification reaction between an alcohol and a carboxylic acid, and may be methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butanoate, ethyl butanoate, lactone, or a combination thereof. To explain further, lactone refers to a compound containing a 1-oxacycloalkan-2-one structure and containing a hydroxyl group and a carboxylic acid, which is condensed within the molecule to form a cyclic carboxylic acid ester monomer, and there are many combinations depending on the position of the cyclic hydroxyl group and the number of carbon atoms in the ring. The lactone may include α-acetolactone (Oxiran-2-one, α-acetolactone), β-propiolactone (Oxetan-2-one, β-propiolactone), γ-butyrolactone (Oxolan-2-one, γ-butyrolactone), γ-valerolactone (5-Methyloxolan-2-one, γ-valerolactone), σ-valerolactone (Oxan-2-one, σ-valerolactone), γ-caprolactone (5-Ethyloxolan-2-one, γ-caprolactone), ε-caprolactone (Oxepan-2-one, ε-caprolactone), δ-gluconolactone (D-Glucono-1, 5-lactone, δ-gluconolactone), or a combination thereof.

[0077] The ether organic solvent described in the present disclosure may be oxolane (THF), 2-methyloxolane (2-MeTHF), 1,3-dioxolane (DOL), 4-methyl-1,3-dioxolane (4-MeDOL), dimethoxymethane (DMM), 1,2-dimethoxyethane (DME), 2,2-dimethoxypropane (DMP), 1,2-bis(2-cyanoethoxy)ethane (DENE), 1-methoxy-2-(2-methoxyethoxy)ethane (DG), or a combination thereof.

[0078] The organic solvent of the sulfur-containing compound described in the present disclosure may be divided into sulfonyl-containing compounds (-(O=)S(=O)-) and sulfonate compounds (-SO2O-). The sulfonyl-containing compounds may include 2,5-Dihydrothiophene-1,1-dioxide and 1-ethenylsulfonylethene. The sulfonate compounds may be further subdivided into mesylate (CH3S02O-), trifluoromethanesulfonate (CF3S02O-), and p-toluenesulfonyl group (Tosyl). The sulfonate may include 1-Methylsulfonyloxyethane, Methyl 4-methylbenzenesulfonate, Oxathiolane 2,2-dione, Prop-1-ene-1,3-sultone, 1,3,2-Dioxathiane 2,2-Dioxide, or combinations thereof.

[0079] Lactone cyclic esters according to the present disclosure may be polycyclic diester monomers formed by the esterification and condensation of two of the same or different compounds, both of which contain a hydroxy acid, and may include glycolide (1,4-dioxane-2,5-dione), lactide (3,6-dimethyl-1,4-dioxane-2,5-dione), or a combination thereof. Based on the stereoisomers formed by differences in the spatial arrangement of atoms, lactide can be further subdivided into LL-lactide ((R,R)-3,6-Dimethyl-1,4-dioxane-2,5-dione, LL-lactide), DD-lactide ((S,S)-3,6-Dimethyl-1,4-dioxane-2,5-dione, DD-lactide), and DL-lactide ((meso)-3,6-Dimethyl-1,4-dioxane-2,5-dione, DL-lactide). or hydroxy-containing carboxylic acid compounds that can be directly copolymerized to form polymers without undergoing a ring-opening reaction, and may include 2-hydroxyacetic acid (glycolic acid), 3-hydroxypropanoic acid (lactic acid), 4-hydroxybutanoic acid, 5-hydroxyvaleric acid, or combinations thereof.

[0080] The cyclic compound additive containing an ether group described in the present disclosure may be a crown ether. Crown ethers have ethyleneoxy (-CH2CH2O-) as the main repeating unit structure, and include 9-crown-3 (1,4,7-trioxonane, 9-Crown-3), 12-crown-4 (1,4,7,10-tetraoxacyclododecane, 12-Crown-4), 15-crown-5 (1,4,7,10,13-pentaoxacyclopentadecane, 15-Crown-5), 18-crown-6 (1,4,7,10,13,16-hexaoxacyclooctadecane, 18-Crown-6), 21-crown-7 (1, 4,7,10,13,16,19-Heptaoxacycloheneicosane, 21-Crown-7), Dibenzo-18-crown-6 (6,7,9,10,17,18,20,21-Octahydrodibenzo[b,k][1,4,7,10,13,16]hexaoxacyclooctadecine, Dibenzo-18-crown-6), Diaza-18-crown-6 (1,4,10,13-tetraoxa-7,16-diazacyclooctadecane, Diaza-18-crown-6), or a combination thereof.

[0081] The aromatic additives described herein may include methoxybenzene, 1-ethynyl-4-methoxybenzene, tert-butylbenzene, fluorobenzene, 1,2-difluorobenzene, 1,1'-oxydibenzene, 1,4-diphenylbenzene, 2-fluoro-4-(2-methyl-2-propanyl)aniline, N-[3-(trimethoxysilyl)propyl]aniline, or combinations thereof.

[0082] The phosphorus-containing compound additive described in the present disclosure may be tris(trimethylsilyl)phosphite (TMSPi), tris(2,2,2-trifluoroethyl)phosphite, triphenyl phosphite, ethoxy(pentafluoro)cyclotriphosphazene (1,3,5,2,4,6-triazatriphosphorine, 2-ethoxy-2,4,4,6,6-pentafluoro-2,2,4,4,6,6-hexahydro), or combinations thereof.

[0083] The boron-containing compound additive described in the present disclosure may be trimethyl borate, tris(trimethylsilyl)borate, trimethylboroxine (2,4,6-trimethyl-1,3,5,2,4,6-trioxatriborinane), or combinations thereof.

[0084] The inorganic oxide additives described in the present disclosure may be composites such as lithium lanthanum zirconium oxide (LiLaZrO), lithium lanthanum zirconium tantalum oxide (LiLaZrTaO), lithium lanthanum titanium oxide (LiLaTiO), lithium phosphate (LiPO), lithium fluorophosphate (LiPOF), lithium titanium phosphate (LiTiPO), lithium aluminum germanium phosphate (LiAlGeP), lithium aluminum titanium phosphate (LiAlTiPO), lithium germanium phosphorus sulfur oxide (LiGePSO), lithium tin phosphorus sulfur oxide (LiSnPSO), lead zirconium titanium oxide (PbZrTiO), lead lanthanum zirconium titanium oxide (PbLaZrTiO), barium titanium oxide (BaTiO), and the like. The inorganic oxide additives may include various different oxidation states or Al2O3, TiO2, SiO2, SnO2, NiO, ZnO, CaO, MgO, ZrO2, CeO2, YO3, etc., and contribute to reducing the crystallinity of the polymer electrolyte, further improving the ionic conductivity and the physical and mechanical strength of the electrolyte, and improving the battery cycle life.

[0085] The separator described in the present disclosure may be a film having a porous structure, and may include a single layer or multilayer film of polyolefin, polyamide, polyester fiber, such as polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), acrylonitrile-butadiene-styrene copolymer (ABS), epoxy resin, or may include at least one inorganic ceramic composite film such as Mg(OH)2, MgO, BaSO4, SnO2, NiO, CaO, Al2O3, ZnO, SiO2, TiO2, or a combination thereof on the surface. The inorganic ceramic composite film may include a variety of different oxidation states.

[0086] Regarding the weight ratio of the negative electrode described in this disclosure, the weight of the negative electrode calculated here does not include the weight of the current collector.

[0087] The number of battery cycles described in this disclosure is defined as the first cycle in which the battery is a commercially available product, and the first test in this state is the first cycle defined in this disclosure, with one discharge and one charge test being one cycle number, and the number of cycles is calculated in this manner.

[0088] The capacity of the battery described in this disclosure can be measured by measuring the charge capacity and discharge capacity of the battery. The capacity can be calculated by the volumetric capacity (mAh / cm 3 Capacity can be divided into volumetric capacity (mAh / g) and gravimetric capacity (mAh / g). Volumetric capacity represents the electrical capacity that can be provided per cubic centimeter of sheet in a battery, and the volume of the current collector must be subtracted in the calculation of volumetric capacity, and gravimetric capacity represents the electrical capacity that can be provided per gram of sheet in a battery, and the volume of the current collector must be subtracted in the calculation of gravimetric capacity, and the sheet may be a positive electrode sheet or a negative electrode sheet.

[0089] The current collector described in the present disclosure may be a substrate made of a metal foil or a conductive polymer, and the metal foil may be selected from aluminum, copper, titanium, nickel, tantalum, stainless steel, or alloys formed by the above.

[0090] The C-rate (C) described in this disclosure can represent the amount of electricity in one hour when the battery is fully discharged, and C can be used as a unit of the charge / discharge current of the battery.

[0091] The battery measurement voltage range described in the present disclosure can be selected as an appropriate voltage range based on the oxidation-reduction potential of the positive and negative electrode materials, and the voltage range may be selected as 0V-5.0V, preferably 0V-3.0V, preferably 1.0V-4.5V, or preferably 2.5V-4.5V.

[0092] The discharge volumetric capacity described in the present disclosure can be expressed as CiVj, and the discharge gravimetric capacity can be expressed as CiGj, where i represents the charge and discharge in C units of electricity, and j represents the number of cycles of the current battery charge and discharge.

[0093] The total number of times that the coulombic efficiency described in this disclosure meets a certain percentage range can be expressed as nxCyEz, where x represents the lower limit of the certain percentage range, y represents the charging and discharging current in C, and z represents the cutoff number of cycles for charging and discharging the battery.

[0094] The average coulombic efficiency described in this disclosure can be expressed as aCyEz, where y represents the amount of electricity in C that is charged and discharged, and z represents the number of cycles at which the battery is charged and discharged at cutoff.

[0095] The particle size described in the present disclosure can be measured by measuring the amplitude over time of light scattered by particles undergoing Brownian motion using dynamic light scattering, and the particle size and particle size distribution can be measured. The particle size can be calculated based on the Stokes-Einstein equation, which is as follows: D = kT / (3πηDf), D is the particle diameter (unit: m), k is the Potsmann constant (unit: J / K), T is the absolute temperature (unit: K), and η is the solvent viscosity (unit: kg×m -1 ×s -1 ), Df is the diffusion coefficient (unit: m 2 ×s -1 ).

[0096] The particle size distribution described in this disclosure represents the particle size distribution of various different sizes of particles in the measured object, and a cumulative particle size distribution function can be obtained based on the ratio of each particle size distribution and the cumulative percentage based on the volume. For example, if the particle size at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, it indicates that the particle size of 50% of the particles in the measured object is smaller than the particle size of D50, and D10 and D90 are also inferred based on this, and unless otherwise specified, D50 is used as the criterion for determining the particle size.

[0097] The core particle size described in the present disclosure can be measured by analyzing the silicon crystal grain diffraction peak {111} using an X-ray diffractometer, and is obtained based on the Scherrer equation. L = (κ × λ) / (β cos(θ / 2)), L is the grain size of the silicon crystal grains (unit: nm), κ is the shape factor (approximately 0.9, but varies depending on the actual shape of the crystal), β is the half-width of the {111} diffraction peak (unit: radian), and θ is the position of the {111} diffraction peak.

[0098] The negative electrode sheets described in this disclosure can be manufactured using single or double layer coating, vacuum plating, composite structures, and the like.

[0099] Roughness as described in this disclosure is defined as the ISO 251781 surface texture parameter Sa (μm) as the arithmetic mean height of the surface, and the area of ​​the roughness measurement region is at least 10,000 μm 2 is set to be greater than , the height of the average plane is the arithmetic mean of the heights of the coordinates Z(x, y) of each point within the area of ​​the region, and Sa is the average value of the absolute values ​​of the height differences of the coordinates Z(x, y) of each point within the area of ​​the region relative to the average plane, then it is obtained based on the following formula.

number

[0100] The electrical conductivity described in the present disclosure is measured by electrochemical impedance spectroscopy (EIS) method, in which an alternating current of 1 Hz to 100 Hz and an amplitude of 50 mV is applied to a polymer or electrolyte, the resistance is measured, and the electrical conductivity is calculated by the following formula. Ci = (1 / R) × (L / A), Ci(S×cm -1 ) is the conductivity, R (Ω) is the resistance, L (cm) is the pitch between the two electrodes, and A (cm 2 ) is the cross-sectional area of ​​the object to be measured and the electrode, and (L / A) is the conductivity coefficient (cm-1 ) can be represented as

[0101] The electrochemical stability described in this disclosure was measured using linear sweep voltammetry (LSV) at a scan rate of 0.1 V / s for Li / Li + Cycle measurements are performed under conditions where the relative voltage is between -5V and 5V, and the corresponding changes in the relationship between the generated current and the potential can be obtained.

[0102] Battery components described in the present disclosure may include a battery housing, an elastomeric sheet, a weight plate, a cover plate, a tab, and a cap.

[0103] The bipolar battery described in the present disclosure may include a bipolar battery sheet and an electrolyte, one side of the bipolar battery sheet is a positive electrode and includes a positive electrode material, the other side is a negative electrode and includes a negative electrode material, two bipolar battery sheets (the electrolyte contacts the positive electrode of one bipolar battery sheet and the negative electrode of another bipolar battery sheet) communicate with each other through the electrolyte to form a bipolar battery cell, and multiple bipolar battery units are connected in series to form a bipolar battery.

[0104] The battery described in the present disclosure can be a primary battery or a secondary battery. The electrochemical carrier of the primary battery or the secondary battery can be at least one of a button carrier, a wound carrier or a laminated carrier, which can be applied to the lightweight and thin design of portable electronic products, such as digital cameras, mobile phones, notebook computers, game console handles, etc., and can also be applied to the large-scale energy storage industry, such as light electric bicycles, electric vehicles, etc.

[0105] Based on the above embodiment, specific examples are proposed below and will be described in detail in combination with experimental data.

[0106] <Comparative Example>

[0107] Please refer to Figure 1. Figure 1 was a scanning electron microscope image of the surface of the core-shell structure of a comparative battery. The comparative battery was a battery, the negative electrode of which included a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that was further away from the center of the core-shell structure than the core material.

[0108] In the battery of the comparative example, the core material contained a structural element oxide, and the structural element oxide contained a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50 = 9278.1 nm and Dtn = 6345.6 nm were satisfied.

[0109] In the battery of the comparative example, the shell material contained a silicon-based material. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material with respect to the core material is PCs, the conditions of sD50=80.0 nm and PCs=0% were satisfied.

[0110] In the battery of the comparative example, when the particle diameter of the niobium titanium composite oxide is taken as Dtn and the particle diameter of the silicon-based material at D50 is taken as sD50, the condition Dtn / sD50=79.3 was satisfied.

[0111] In the comparative example battery, when the weight of the core material in the negative electrode is tWc and the weight of the silicon-based material in the negative electrode is tWs, the conditions of tWc = 1.00, tWs = 0.05, and tWc / tWs = 20.0 were satisfied.

[0112] Detailed data of the comparative battery is shown in Table 1 below.

[0113] <First Example>

[0114] Please refer to Figures 2A, 2B, 3 and 4. Figure 2A is a scanning electron microscope image of the surface of the core-shell structure of the battery of the first embodiment, and Figure 2B is a 0.02×πR 2 μm 2FIG. 3 is a scanning electron microscope image of the surface of the core-shell structure of Example 1, and FIG. 4 is a superposition result of the scanning electron microscope image and the element position distribution image of the surface of the core-shell structure of Example 1. Example 1 is a battery, the negative electrode of which includes a composition, the composition includes a core-shell structure, and the core-shell structure includes a core material and a shell material that is farther away from the center of the core-shell structure than the core material.

[0115] In the battery of the first embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=9278.1 nm and Dtn=6957.3 nm are satisfied.

[0116] In the battery of the first embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=27.0% are satisfied.

[0117] In the first example battery, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0118] In the battery of the first embodiment, when the particle size of the core material at D50 is cD50 and the particle size of the silicon-based material at D50 is sD50, the condition cD50 / sD50=116.0 was satisfied.

[0119] In the battery of the first embodiment, when the particle diameter of the niobium titanium composite oxide is taken as Dtn and the particle diameter of the silicon-based material at D50 is taken as sD50, the condition Dtn / sD50=87.0 was satisfied.

[0120] In the battery of the first embodiment, when the total number of particles of the niobium titanium composite oxide in the core-shell structure is Qtn and the total number of particles of the silicon-based material in the core-shell structure is Qs, the condition Log(Qs / Qtn)=3.9 was satisfied.

[0121] In the battery of the first embodiment, when the weight of the niobium titanium composite oxide relative to the core-shell structure is Wtn and the weight of the silicon-based material relative to the core-shell structure is Ws, the condition Wtn / Ws=148.7 was satisfied.

[0122] In the battery of the first embodiment, when the weight of the core material in the negative electrode is tWc and the weight of the silicon-based material in the negative electrode is tWs, the conditions of tWc = 9.00, tWs = 1.00, and tWc / tWs = 9.0 were satisfied.

[0123] Detailed data of the battery of the first embodiment is shown in Table 1 below.

[0124] <Second Example>

[0125] A second example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from the center of the core-shell structure than the core material.

[0126] In the battery of the second embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=9278.1 nm and Dtn=7958.7 nm are satisfied.

[0127] In the battery of the second embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=50.7% are satisfied.

[0128] In the battery of the second embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0129] Detailed data of the battery of the second embodiment are shown in the following Table 1. All other parameter definitions in Table 1 of the second embodiment are similar to those of the first embodiment, and are not further described here. [Table 1-1] [Table 1-2]

[0130] <Third Example>

[0131] A third example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from the center of the core-shell structure than the core material.

[0132] In the battery of the third embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=13085.2 nm and Dtn=15688.6 nm are satisfied.

[0133] In the battery of the third embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=86.8% are satisfied.

[0134] In the battery of the third embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0135] Detailed data of the battery of the third embodiment are shown in the following Table 2. All other parameter definitions in Table 2 of the third embodiment are similar to those of the first embodiment, and are not further described here.

[0136] <Fourth Example>

[0137] A fourth example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0138] In the battery of the fourth embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=16011.6 nm and Dtn=13490.2 nm are satisfied.

[0139] In the battery of the fourth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=81.1% are satisfied.

[0140] In the battery of the fourth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0141] Detailed data of the battery of the fourth embodiment are shown in the following Table 2. All other parameter definitions in Table 2 of the fourth embodiment are similar to those of the first embodiment, and are not further described here.

[0142] <Fifth Example>

[0143] A fifth example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0144] In the battery of the fifth embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=10749.6 nm and Dtn=18914.9 nm are satisfied.

[0145] In the battery of the fifth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=58.2% are satisfied.

[0146] In the battery of the fifth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0147] Detailed data of the battery of the fifth embodiment are shown in the following Table 2. All other parameter definitions in Table 2 of the fifth embodiment are similar to those of the first embodiment, and are not further described here. [Table 2-1] [Table 2-2]

[0148] <Sixth Example>

[0149] A sixth example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from the center of the core-shell structure than the core material.

[0150] In the battery of Example 6, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=13704.9 nm and Dtn=17703.4 nm are satisfied.

[0151] In the battery of the sixth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=68.6% are satisfied.

[0152] In the battery of the sixth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0153] Detailed data of the battery of the sixth embodiment are shown in the following Table 3. All other parameter definitions in Table 3 of the sixth embodiment are similar to those of the first embodiment, and are not further described here.

[0154] <Seventh Example>

[0155] A seventh example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from the center of the core-shell structure than the core material.

[0156] In the battery of the seventh embodiment, the core material contains a structural element oxide, and the structural element oxide contains a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=12546.6 nm and Dtn=5080.8 nm are satisfied.

[0157] In the battery of the seventh embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=64.4% are satisfied.

[0158] In the seventh example battery, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0159] Detailed data of the battery of the seventh embodiment are shown in the following Table 3. All other parameter definitions in Table 3 of the seventh embodiment are similar to those of the first embodiment, and are not further described here.

[0160] <Eighth Example>

[0161] An eighth example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0162] In the battery of Example 8, the core material contained a structural element oxide, and the structural element oxide contained a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=9952.2 nm and Dtn=6834.9 nm were satisfied.

[0163] In the battery of Example 8, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=66.3% are satisfied.

[0164] In the battery of the eighth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0165] Detailed data of the battery of the eighth embodiment are shown in the following Table 3. All other parameter definitions in Table 3 of the eighth embodiment are similar to those of the first embodiment, and are not further described here. [Table 3-1] [Table 3-2]

[0166] <Ninth Example>

[0167] A ninth example is a battery, the negative electrode of which includes a composition, the composition including a core-shell structure, the core-shell structure including a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0168] In the battery of Example 9, the core material contained a structural element oxide, and the structural element oxide contained a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50 and the particle diameter of the niobium titanium composite oxide is Dtn, the conditions of cD50=4099.1 nm and Dtn=4107.2 nm were satisfied.

[0169] In the battery of Example 9, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=41.2% are satisfied.

[0170] In the battery of the ninth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0171] Detailed data of the battery of the ninth embodiment are shown in the following Table 4. All other parameter definitions in Table 4 of the ninth embodiment are similar to those of the first embodiment, and are not further described here.

[0172] <Tenth Example>

[0173] A tenth embodiment is a battery, the negative electrode of which comprises a composition, the composition comprising a core-shell structure, the core-shell structure comprising a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0174] In the battery of Example 10, the core material contained a structural element oxide, and the structural element oxide contained a niobium titanium composite oxide. When the particle diameter of the core material at D50 is cD50, the condition of cD50=14935.3 nm was satisfied.

[0175] In the battery of the tenth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50 and the coverage rate of the silicon-based material to the core material is PCs, the conditions of sD50=80.0 nm and PCs=32.0% are satisfied.

[0176] In the battery of the tenth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was dimethylaminoethyl acrylate.

[0177] Detailed data of the battery of the tenth embodiment are shown in the following Table 4. All other parameter definitions in Table 4 of the tenth embodiment are similar to those of the first embodiment, and are not further described here.

[0178] <Eleventh Example>

[0179] An eleventh embodiment is a battery, the negative electrode of which comprises a composition, the composition comprising a core-shell structure, the core-shell structure comprising a core material and a shell material that is further from the center of the core-shell structure than the core material.

[0180] In the battery of Example 11, the core material contained a structural element oxide, and the structural element oxide contained a lithium titanium composite oxide. When the particle diameter of the core material at D50 is cD50, the condition of cD50=28439.3 nm was satisfied.

[0181] In the battery of Example 11, the shell material included a mixed material, the mixed material included a modified silicon material, and the modified silicon material included a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50, the condition of sD50 = 80.0 nm was satisfied.

[0182] In the battery of the eleventh embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was acrylic acid.

[0183] Detailed data of the battery of the eleventh embodiment are shown in the following Table 4. All other parameter definitions in Table 4 of the eleventh embodiment are similar to those of the first embodiment, and are not further described here. [Table 4-1] [Table 4-2]

[0184] <Twelfth Example>

[0185] A twelfth example is a battery, the negative electrode of which comprises a composition, the composition comprising a core-shell structure, the core-shell structure comprising a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0186] In the battery of Example 12, the core material contained a structural element oxide, and the structural element oxide contained a structural element composite oxide. When the particle diameter of the core material at D50 is cD50, the condition of cD50=595.6 nm was satisfied.

[0187] In the battery of the twelfth embodiment, the shell material includes a mixed material, the mixed material includes a modified silicon material, and the modified silicon material includes a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50, the condition of sD50=80.0 nm is satisfied.

[0188] In the battery of the twelfth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was methyl methacrylate.

[0189] Detailed data of the battery of the 12th embodiment are shown in the following Table 5. All other parameter definitions in Table 5 of the 12th embodiment are similar to those of the first embodiment, and are not further described here.

[0190] <Thirteenth Example>

[0191] A thirteenth embodiment is a battery, the negative electrode of which comprises a composition, the composition comprising a core-shell structure, the core-shell structure comprising a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0192] In the battery of Example 13, the core material contained a structural element oxide, and the structural element oxide contained a structural element composite oxide. When the particle diameter of the core material at D50 is cD50, the condition of cD50=606.6 nm was satisfied.

[0193] In the battery of Example 13, the shell material included a mixed material, the mixed material included a modified silicon material, and the modified silicon material included a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50, the condition of sD50=80.0 nm was satisfied.

[0194] In the battery of the thirteenth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was methyl acrylate.

[0195] Detailed data of the battery of the thirteenth embodiment are shown in the following Table 5. All other parameter definitions in Table 5 of the thirteenth embodiment are similar to those of the first embodiment, and are not further described here.

[0196] <14th Example>

[0197] A fourteenth embodiment is a battery, the negative electrode of which comprises a composition, the composition comprising a core-shell structure, the core-shell structure comprising a core material and a shell material that is further away from a center of the core-shell structure than the core material.

[0198] In the battery of Example 14, the core material contained a carbon active material, and the carbon active material contained graphite. When the particle diameter of the core material at D50 is cD50, the condition of cD50=13290.0 nm was satisfied.

[0199] In the battery of Example 14, the shell material included a mixed material, the mixed material included a modified silicon material, and the modified silicon material included a silicon-based material and a polymer. When the particle size of the silicon-based material at D50 is sD50, the condition of sD50 = 80.0 nm was satisfied.

[0200] In the battery of the fourteenth embodiment, the polymer was polymerized by at least two kinds of monomers, the at least two kinds of monomers included a first monomer and a second monomer, the first monomer was (meth)acryloylpropyltrimethoxysilane, and the second monomer was isooctyl acrylate.

[0201] Detailed data of the battery of the 14th embodiment are shown in the following Table 5. All other parameter definitions in Table 5 of the 14th embodiment are similar to those of the first embodiment, and are not further described here. [Table 5-1] [Table 5-2]

[0202] Although the contents of the present disclosure have been disclosed in the above embodiments, the above embodiments are not intended to limit the contents of the present disclosure, and anyone skilled in the art can make various changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the protection scope of the present disclosure is limited to the scope of the attached patent application.

Claims

1. 1. A composition comprising: a core-shell structure including a core material and a shell material, the shell material being further away from a center of the core-shell structure than the core material; The core material includes a structural element oxide, the structural element oxide includes a structural element, and the structural element is at least two selected from the group consisting of lithium, titanium, niobium, cobalt, copper, tin, silicon, iron, manganese, and nickel; A composition, wherein the shell material comprises a blended material, the blended material comprising a modified silicone material, the modified silicone material comprising a silicone-based material and a polymer.

2. The particle diameter at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, If the particle size of the core material at D50 is cD50, The composition according to claim 1, which satisfies the condition: 100.0 nm≦cD50≦80000.0 nm.

3. The particle diameter at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, If the particle size of the silicon-based material at D50 is sD50, The composition according to claim 1, which satisfies the condition: 10.0 nm≦sD50≦3000.0 nm.

4. The particle diameter at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, If the particle size of the core material at D50 is cD50 and the particle size of the silicon-based material at D50 is sD50, The composition according to claim 1, which satisfies the condition: 1.0≦cD50 / sD50≦8000.

0.

5. The composition according to claim 4 , wherein the weight of the core material in the core-shell structure is greater than the weight of the silicon-based material in the core-shell structure.

6. The composition according to claim 1 , wherein the structural element oxide is a niobium titanium composite oxide.

7. When the weight of the niobium titanium composite oxide relative to the core-shell structure is Wtn and the weight of the silicon-based material relative to the core-shell structure is Ws, The composition according to claim 6, which satisfies the condition 10.0≦Wtn / Ws≦500.

0.

8. The composition according to claim 6, wherein the niobium titanium composite oxide is a doped niobium titanium composite oxide.

9. 9. The composition according to claim 8, wherein the doped niobium titanium composite oxide comprises at least one doping element, the at least one doping element being at least one selected from the group consisting of lithium, manganese, magnesium, iron, copper, cobalt, gallium, tantalum, tungsten, fluorine, phosphorus, sodium and molybdenum.

10. 10. The composition of claim 9, wherein the at least one doping element is at least one selected from the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus.

11. The polymer is polymerized with at least two types of monomers, the at least two types of monomers including a first monomer and a second monomer; the first monomer includes a siloxane group, and the second monomer includes a carboxyl group or an ester group; The composition of claim 1 , wherein the first monomer is closer to the silicon-based material than the second monomer.

12. The composition of claim 11 , wherein the silicon-based material and the polymer are covalently bonded.

13. The composition of claim 1 , wherein the mixed material further comprises a carbon-based material.

14. A negative electrode comprising the composition of claim 1.

15. If the weight of the core material in the negative electrode is tWc and the weight of the silicon-based material in the negative electrode is tWs, The negative electrode according to claim 14, which satisfies the condition: 0.1≦tWc / tWs≦100.

0.

16. A battery comprising the negative electrode of claim 14.

17. If the maximum value of the discharge volume capacity of the battery from the first cycle to the 20th cycle is VMax, 100mAh / cm 3 ≦VMax≦800mAh / cm 3 The battery according to claim 16, which satisfies the following condition.

18. If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 10th cycle is V10, The battery according to claim 16, which satisfies the condition 0.85≦V10 / V5.

19. If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 50th cycle is V50, The battery according to claim 16, which satisfies the condition 0.80≦V50 / V5.

20. If the discharge volume capacity of the battery at the 5th cycle is V5 and the discharge volume capacity of the battery at the 100th cycle is V100, The battery according to claim 16, which satisfies the condition 0.70≦V100 / V5.

21. Let n90E20 be the total number of times that the coulombic efficiency of the previous 20 cycles of the battery is greater than 90% and less than 110%. The battery according to claim 16, which satisfies the condition: 15≦n90E20≦20.

22. 1. A composition comprising: a core-shell structure including a core material and a shell material, the shell material being further away from a center of the core-shell structure than the core material; The core material includes a structural element oxide, and the structural element oxide includes a niobium titanium composite oxide; the shell material comprises a composite material, the composite material comprising a silicon-based material; If the coverage of the silicon-based material with respect to the core material is PCs, A composition satisfying the condition: 20.0%≦PCs≦100.0%.

23. When the total number of particles of the niobium titanium composite oxide in the core-shell structure is Qtn and the total number of particles of the silicon-based material in the core-shell structure is Qs, The composition according to claim 22, which satisfies the condition: 0.1≦Log(Qs / Qtn)<10.

0.

24. If the coverage of the silicon-based material with respect to the core material is PCs, The composition of claim 23, which satisfies the condition: 40.0%≦PCs≦95.0%.

25. When the total number of particles of the niobium titanium composite oxide in the core-shell structure is Qtn and the total number of particles of the silicon-based material in the core-shell structure is Qs, The composition according to claim 24, which satisfies the condition: 2.5≦Log(Qs / Qtn)≦7.

5.

26. The particle diameter at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, When the particle diameter of the niobium titanium composite oxide is Dtn and the particle diameter of the silicon-based material at D50 is sD50, The composition according to claim 22, which satisfies the condition: 20.0≦Dtn / sD50≦500.

0.

27. The composition according to claim 22, wherein the niobium titanium composite oxide is a doped niobium titanium composite oxide.

28. 28. The composition of claim 27, wherein the doped niobium titanium composite oxide comprises at least one doping element, and the at least one doping element is at least one selected from the group consisting of lithium, manganese, magnesium, iron, copper, fluorine and phosphorus.

29. When the weight of the niobium titanium composite oxide relative to the core-shell structure is Wtn and the weight of the silicon-based material relative to the core-shell structure is Ws, The composition according to claim 28, which satisfies the condition: 20.0≦Wtn / Ws≦300.

0.

30. 23. A negative electrode comprising the composition of claim 22.

31. A battery comprising the negative electrode of claim 30.

32. 1. A composition comprising: a core-shell structure including a core material and a shell material, the shell material being further away from a center of the core-shell structure than the core material; The core material is at least one selected from the group consisting of carbon active material, structural element mixed oxide, and tin-based alloy; the shell material comprises a mixed material, the mixed material comprises a modified silicone material, the modified silicone material comprises a silicone-based material and a polymer, the polymer comprises a siloxane group; The particle diameter at which the percentage of the cumulative particle size distribution reaches 50% is defined as D50, If the particle size of the core material at D50 is cD50 and the particle size of the silicon-based material at D50 is sD50, A composition satisfying the condition: 1.0≦cD50 / sD50≦8000.

0.

33. If the particle size of the core material at D50 is cD50 and the particle size of the silicon-based material at D50 is sD50, The composition according to claim 32, which satisfies the condition: 50.0≦cD50 / sD50≦500.0.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary battery and method for producing the same

    JP2014022294A

  • Active material for batteries, method for manufacturing the same, nonaqueous electrolyte battery, and battery pack

    JP2015084321A

  • Coated lithium-nickel complex oxide particle and method for manufacturing coated lithium-nickel complex oxide particles

    JP2016009524A

  • Electrode for lithium ion battery

    JP2021144797A

  • Active material having surface coat layer, electrode comprising same, and electricity storage device

    WO2021090656A1